(2x+1)-2(x-5)+6=3x(x+1)+(x-1)+23

Simple and best practice solution for (2x+1)-2(x-5)+6=3x(x+1)+(x-1)+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+1)-2(x-5)+6=3x(x+1)+(x-1)+23 equation:


Simplifying
(2x + 1) + -2(x + -5) + 6 = 3x(x + 1) + (x + -1) + 23

Reorder the terms:
(1 + 2x) + -2(x + -5) + 6 = 3x(x + 1) + (x + -1) + 23

Remove parenthesis around (1 + 2x)
1 + 2x + -2(x + -5) + 6 = 3x(x + 1) + (x + -1) + 23

Reorder the terms:
1 + 2x + -2(-5 + x) + 6 = 3x(x + 1) + (x + -1) + 23
1 + 2x + (-5 * -2 + x * -2) + 6 = 3x(x + 1) + (x + -1) + 23
1 + 2x + (10 + -2x) + 6 = 3x(x + 1) + (x + -1) + 23

Reorder the terms:
1 + 10 + 6 + 2x + -2x = 3x(x + 1) + (x + -1) + 23

Combine like terms: 1 + 10 = 11
11 + 6 + 2x + -2x = 3x(x + 1) + (x + -1) + 23

Combine like terms: 11 + 6 = 17
17 + 2x + -2x = 3x(x + 1) + (x + -1) + 23

Combine like terms: 2x + -2x = 0
17 + 0 = 3x(x + 1) + (x + -1) + 23
17 = 3x(x + 1) + (x + -1) + 23

Reorder the terms:
17 = 3x(1 + x) + (x + -1) + 23
17 = (1 * 3x + x * 3x) + (x + -1) + 23
17 = (3x + 3x2) + (x + -1) + 23

Reorder the terms:
17 = 3x + 3x2 + (-1 + x) + 23

Remove parenthesis around (-1 + x)
17 = 3x + 3x2 + -1 + x + 23

Reorder the terms:
17 = -1 + 23 + 3x + x + 3x2

Combine like terms: -1 + 23 = 22
17 = 22 + 3x + x + 3x2

Combine like terms: 3x + x = 4x
17 = 22 + 4x + 3x2

Solving
17 = 22 + 4x + 3x2

Solving for variable 'x'.

Combine like terms: 17 + -22 = -5
-5 + -4x + -3x2 = 22 + 4x + 3x2 + -22 + -4x + -3x2

Reorder the terms:
-5 + -4x + -3x2 = 22 + -22 + 4x + -4x + 3x2 + -3x2

Combine like terms: 22 + -22 = 0
-5 + -4x + -3x2 = 0 + 4x + -4x + 3x2 + -3x2
-5 + -4x + -3x2 = 4x + -4x + 3x2 + -3x2

Combine like terms: 4x + -4x = 0
-5 + -4x + -3x2 = 0 + 3x2 + -3x2
-5 + -4x + -3x2 = 3x2 + -3x2

Combine like terms: 3x2 + -3x2 = 0
-5 + -4x + -3x2 = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(5 + 4x + 3x2) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(5 + 4x + 3x2)' equal to zero and attempt to solve: Simplifying 5 + 4x + 3x2 = 0 Solving 5 + 4x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 1.666666667 + 1.333333333x + x2 = 0 Move the constant term to the right: Add '-1.666666667' to each side of the equation. 1.666666667 + 1.333333333x + -1.666666667 + x2 = 0 + -1.666666667 Reorder the terms: 1.666666667 + -1.666666667 + 1.333333333x + x2 = 0 + -1.666666667 Combine like terms: 1.666666667 + -1.666666667 = 0.000000000 0.000000000 + 1.333333333x + x2 = 0 + -1.666666667 1.333333333x + x2 = 0 + -1.666666667 Combine like terms: 0 + -1.666666667 = -1.666666667 1.333333333x + x2 = -1.666666667 The x term is 1.333333333x. Take half its coefficient (0.6666666665). Square it (0.4444444442) and add it to both sides. Add '0.4444444442' to each side of the equation. 1.333333333x + 0.4444444442 + x2 = -1.666666667 + 0.4444444442 Reorder the terms: 0.4444444442 + 1.333333333x + x2 = -1.666666667 + 0.4444444442 Combine like terms: -1.666666667 + 0.4444444442 = -1.2222222228 0.4444444442 + 1.333333333x + x2 = -1.2222222228 Factor a perfect square on the left side: (x + 0.6666666665)(x + 0.6666666665) = -1.2222222228 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 4(7v-2)-7=4(1+7v) | | 4k(3+k)=-(2k+3) | | -9(z+5)=0 | | -9(z+6)=0 | | x(x-3)-x(x+5)+6=-2 | | 1-7n-2n=-8 | | 7-a=15a-2a | | -16x^2+3x+1.3=0 | | (23+5x)=(14x-3) | | 3(n-8)=4(n+2) | | (2n+5)(2n+3)=0 | | R=5x+43 | | (4g+7)+(7g+2)= | | 23+5x=14x-3 | | 4(c-3)+5=2c+3 | | 6(m+1)=3m-3 | | -3(a+4)=6 | | -g+6+2g=4g+4 | | 6x+7=2x-13 | | 12-1.7x=4.15 | | (x+1)+2(x-3)-5=(x+2)-(x+3)+2 | | ln(5x+3)=4 | | 27-3(2x+3)=2(1-3x) | | 7-n-6=-13+6n | | 12x^2+9x-20=0 | | 5(2.6x+3.9)=5 | | cos(2x)-5cosx+3=o | | .5x+7=2x+14 | | 1-4=7 | | 18-8(x+2)=2(x-9) | | 3x+5=-6x+32 | | -2/5(5x-20y) |

Equations solver categories